Effects on structure and properties of Zr55Al 10Cu30Ni5 metallic glass irradiated by high intensity pulsed ion beam; Applied Surface Science; Vol. 313 - Liu X.; Mei X.; Qiang J.; Remnev G. E. Gennady Efimovich; Wang Y. (2014, 2014)
Title screen